THE ROLE OF COMPACTNESS IN ACHIEVING URBAN SUSTAINABILITY (CAHIERS MAGELLANES-NS, 2024)
The compact city is one of the leading models of sustainable urbanism. Over the past thirty years, the planning and development of compact cities have been a primary response to the challenges of sustainable development. This model has received substantial support from global policies due to its effective contribution to achieving environmental, economic, and social sustainability goals. The compact city represents the ideal city for achieving urban sustainability. to respond to many urban problems through high densities, mixed use and integration of urban elements., In order to ensure easy access to services and more efficient use of infrastructure, and its reliance on sustainable means of transportation to preserve the environment from polluting emissions. The research deals with the compact city model and its characteristics in urban planning and development in relation to the three dimensions of sustainability. and study the possibility of having a high-density city as a sustainable urban model. To shed light on this urban phenomenon, the theoretical framework extract was applied to a compact Arab city model, namely the city of Dubai, Business Bay area.